Appraising community driven health research with Aboriginal and Torres Strait Islander communities: a scoping review using the Aboriginal and Torres Strait Islander Quality Appraisal Tool. (26th September 2022) - Biles, Brett; Biles, Jessica; Friere, Kate; Deravin, Linda; Lawrence, Jayne; Yashadhana, Aryati
Summary: Most research involving Aboriginal and Torres Strait Islander peoples has been conducted by non-Indigenous people and has not been a positive experience for many Aboriginal and Torres Strait Islander communities. This scoping review maps approaches to health research involving Aboriginal and Torres Strait Islander peoples and communities in Australia from the last two decades. A literature search found 198 papers, of which 34 studies met the inclusion criteria. The Aboriginal and Torres Strait Islander Quality Appraisal Tool was then used to map the quality of the reported community driven research. The Quality Appraisal Tool privileges, Aboriginal and Torres Strait Islander people's epistemologies and ethical research governance. The findings reported on strengths and identified areas for improvement in reporting community driven research. Lay Summary: Through scooping design this study sought to comprehensively map published community driven health research with Aboriginal and Torres Strait Islander communities in the past two decades. Using the Aboriginal and Torres Strait Islander Quality Appraisal Tool the we were able to identify key strengths and areas for improvement that will guide researchers reporting on research focussed on Aboriginal and Torres Strait Islander peoples and communities.